2018
DOI: 10.3390/ijms19051446
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Receptor 1 Is Involved in Non-Obese Diabetic Mouse Thymocyte Migration Disorders

Abstract: NOD (non-obese diabetic) mice spontaneously develop type 1 diabetes following T cell-dependent destruction of pancreatic β cells. Several alterations are observed in the NOD thymus, including the presence of giant perivascular spaces (PVS) filled with single-positive (SP) CD4+ and CD8+ T cells that accumulate in the organ. These cells have a decreased expression of membrane CD49e (the α5 integrin chain of the fibronectin receptor VLA-5 (very late antigen-5). Herein, we observed lower sphingosine-1-phosphate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…The authors found that young female NOD mice who later progress to autoimmune diabetes exhibited the same lipidomic pattern as prediabetic children [164], confirming that the NOD mouse is a valuable model to study the role of SLs in T1DM development. Moreover, NOD thymocytes were found to be characterized by a lower level of S1PR1 and a decreased SPL mRNA and protein expression comparing with healthy mice [177]. These changes were suggested to participate in the T-cell migratory abnormalities observed in NOD mice during diabetes development [177].…”
Section: Animal Modelsmentioning
confidence: 96%
See 2 more Smart Citations
“…The authors found that young female NOD mice who later progress to autoimmune diabetes exhibited the same lipidomic pattern as prediabetic children [164], confirming that the NOD mouse is a valuable model to study the role of SLs in T1DM development. Moreover, NOD thymocytes were found to be characterized by a lower level of S1PR1 and a decreased SPL mRNA and protein expression comparing with healthy mice [177]. These changes were suggested to participate in the T-cell migratory abnormalities observed in NOD mice during diabetes development [177].…”
Section: Animal Modelsmentioning
confidence: 96%
“…Moreover, NOD thymocytes were found to be characterized by a lower level of S1PR1 and a decreased SPL mRNA and protein expression comparing with healthy mice [177]. These changes were suggested to participate in the T-cell migratory abnormalities observed in NOD mice during diabetes development [177]. S1P was shown to reduce CD4+ T-cell activation in NOD mice and to prevent vascular complications [178].…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormonal imbalance in the thymus can be involved in the control of the physiology of the organ in NOD mice and humans, as the properly maturation of the cells, cell adhesion, migration, accumulation and egress, by the modulation of ECM molecules and integrins, chemokines and chemokine receptors, sphingosine-1-phosphate and sphingosine-1-phosphate receptor 1 ( 10 , 64 , 65 , 89 ). As an example, GH/IGF-1 axis can modulate the expression of cytokines, chemokines and ECM molecules and receptors in the thymus ( 61 ).…”
Section: Future Developments and Concluding Remarksmentioning
confidence: 99%
“…In spite of the relatively brief history of sphingosine-1-phosphate (S1P) as a biologically active lipid mediator, numerous reports highlight its major regulatory function in embryogenesis [1,2], the immune system and inflammation [3][4][5], the cardiovascular system [6][7][8][9][10], the nervous system [11][12][13], oncogenesis [14][15][16][17], as well as cellular motility and migration [18][19][20][21]. In the cardiovascular system, S1P has been implicated in the regulation of vasculo-and angiogenesis [22,23] and endothelial barrier function [24][25][26].…”
Section: Introductionmentioning
confidence: 99%